A short review on leptospirosis: Clinical manifestations, diagnosis and treatment - Chinju Susan Chacko; Shravya Lakshmi S; Anjali Jayakumar; Steffy Ligi Binu; Ramesh Datta Pant; Ashish Giri; Sharad Chand; Nandakumar UP (Elsevier, 2021)
In the last few decades, leptospirosis has emerged globally as a fatal infectious disease. Yet, an understanding of the pathogenesis of leptospirosis continues to remain within the grey areas of scientific evidence. In a majority of the cases, the infections are asymptomatic. The benchmark test for leptospirosis is the microscopic agglutination test, commonly known as the MAT test. The standard of treatment is oral doxycycline, although penicillin and azithromycin can also be used. In this review, we aim to elaborately discuss the symptoms, diagnosis and the approved therapeutic regimen of leptospirosis.